STUDI PEMETAAN SOSIAL MASYARAKAT PESISIR di KAMPUNG TELUK SEMANTING KECAMATAN PULAU DERAWAN KABUPATEN BERAU - Dedi Safriyawan; Bambang Indratno Gunawan; Juliani (2339-1324, 2017)
This study aims to identify and map the types of livelihoods and analyze social actors' access to coastal resources, the research was conducted in April until the month of August 2015. Location of the research conducted in Kampung Teluk Semanting Derawan Island District of Berau District. Data collected by survey method that combines qualitative and quantitative approaches. The collection of primary data obtained by observation and conduct in-depth interviews (in-depth) with respondents and key informants (key informant) with various categories of social actors include the RT, retainer, community leaders, the chairman of the group of fishermen, fishing and the woman / wife processing of fishery products. Results from this study indicate that there is a diversity results-based livelihoods arrest and the opening of farmland that causes the growth of diversification in the community. And also from the discussion in the focus group forums, communities are not mutually affect the respective opinions of the FGD.